Behavioral interventions in epilepsy. Issue 2 (April 2019) - Haut, Sheryl R.; Gursky, Jonathan M.; Privitera, Michael
Abstract : Purpose of review: Behavioral intervention describes multiple modalities of treatments which are of increasing interest in epilepsy. This review addresses recent behavioral clinical trials in epilepsy including cognitive behavioral therapy (CBT), mindfulness, progressive muscle relaxation (PMR), and self-management. Results and conclusions from updated Cochrane reviews and the recent International League Against Epilepsy Psychology task force are presented. Recent findings: Two recent large randomized controlled trials (mindfulness and progressive muscle relaxation) reported improved seizure frequency with behavioral treatments. In both studies, participants in both the active and the attentional control arms showed significant seizure reduction, whereas quality of life and stress reduction were better noted in the active arms. Additional behavioral modalities have reported improved seizure control including yoga, bio/neurofeedback, and music therapy. Significant improvements in multiple quality of life, cognitive domains, and medication adherence have been reported from randomized and open label trials of cognitive behavioral therapy, and self-management programs. Multiple promising self-management programs have been recently reported, often utilizing the power of web-based apps, and digitally delivered group therapy. In 2018, the International League Against Epilepsy Psychology task force recommended that 'psychological interventions should be incorporated into comprehensive epilepsy care.' Summary: Behavioral treatments are successful and likely underutilized in the treatment of epilepsy. Given the challenge of conducting randomized clinical trials of behavioral therapy, much remains to be studied. However, for motivated and interested patients, appropriately chosen behavioral therapies appear to be important adjuncts to standard therapy. The timing is currently optimal to take best advantage of smartphone apps and web-based delivery systems, both for research and therapeutic purposes.